2015
DOI: 10.1128/jvi.01560-15
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV-1 Envelope-Specific Breast Milk IgA Responses with Reduced Risk of Postnatal Mother-to-Child Transmission of HIV-1

Abstract: Infants born to HIV-1-infected mothers in resource-limited areas where replacement feeding is unsafe and impractical are repeatedly exposed to HIV-1 throughout breastfeeding. Despite this, the majority of infants do not contract HIV-1 postnatally, even in the absence of maternal antiretroviral therapy. This suggests that immune factors in breast milk of HIV-1-infected mothers help to limit vertical transmission. We compared the HIV-1 envelope-specific breast milk and plasma antibody responses of clade C HIV-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
2
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 44 publications
0
61
2
1
Order By: Relevance
“…Breast milk from HIV-infected women contains protective Env-specific antibodies (6,8,17,42), the presence of which makes development of a maternal HIV vaccine to enhance these preexisting responses an attractive strategy to prevent breastfeeding transmission of HIV. In this study, we gained further understanding of the isotypes, specificities, and functions of HIV-specific breast milk antibody responses induced by i.n./i.m.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast milk from HIV-infected women contains protective Env-specific antibodies (6,8,17,42), the presence of which makes development of a maternal HIV vaccine to enhance these preexisting responses an attractive strategy to prevent breastfeeding transmission of HIV. In this study, we gained further understanding of the isotypes, specificities, and functions of HIV-specific breast milk antibody responses induced by i.n./i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast milk from both HIV-infected humans and SIV-infected rhesus monkeys contains higher-magnitude Envspecific IgG than IgA, in our recent analysis of breast milk antibody responses of women from the Breastfeeding Antiretrovirals and Nutrition (BAN) study, only breast milk HIV envelope gp140-specific IgA was associated with reduced risk of postnatal HIV-1 acquisition (6,7,17). These results suggest that a maternal vaccine with the ability to elicit robust IgA responses in milk could potentially be protective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent human studies demonstrated that HIVspecific breast milk IgA levels could reduce the risk of HIV acquisition in human infants (63). A subsequent study by the same group showed that strong HIV Env-specific IgA responses could be induced in lactating macaques by vaccination (64).…”
Section: Figmentioning
confidence: 99%
“…(20) was measured using a Luc-based ADCC assay according to a previously described procedure (21,22). Cryopreserved PBMCs were used as a source of effector cells (effector-to-target cell ratio, 30:1).…”
Section: Construction Of Linear Ig Expression Cassettesmentioning
confidence: 99%